Globalisation, health and foreign policy: emerging linkages and interests - Roberts Olivia; Owen John (BMC, 2005)
Abstract A discussion of the growing links between the issues of globalisation, health and foreign policy. This article examines the effect this has on health, development and foreign policy communities in the UK and internationally and considers what steps the policy community must take to address the challenges and opportunities of this new relationship.